Preschool depression: clinical course, risk pathways, and early intervention strategies - Pontillo, Maria; Di Vincenzo, Cristina; Bertoncini, Ilaria; Pastore, Chiara; Villani, Valeria; D’Amario, Giulia; Vicari, Stefano (Frontiers in Psychiatry, 2025)
Preschool-onset depression is increasingly recognized as a valid and clinically significant disorder, distinct from developmentally normative sadness and irritability. This mini-review synthesizes principal findings on its clinical presentation, risk and protective factors, developmental course, and evidence-based treatments. A narrative review approach was adopted. Research studies were selected based on key topics, including preschool depression, associated risk and protective factors, developmental trajectories, and treatment approaches, using PubMed as the primary database. Studies were selected based on their relevance to preschool-aged children (3-6 years) and their contribution to the understanding of clinical presentation, longitudinal course, etiological mechanisms, and intervention strategies. Included sources comprised longitudinal cohort studies, randomized controlled trials, and neuroimaging investigations. Preschool depression is associated with specific symptom patterns, such as anhedonia, guilt, and emotional dysregulation. Key risk factors include genetic predisposition, parental psychopathology, early adversity, and temperamental vulnerability. Protective factors such as effortful control and secure attachment appear to mitigate developmental risk. Longitudinal studies confirm both homotypic and heterotypic continuity into adolescence. Among emerging treatments, Parent-Child Interaction Therapy – Emotion Development shows strong empirical support, targeting both symptom reduction and emotional competence. Preschool depression represents a distinct condition with significant implications for long-term mental health. Early identification and intervention, particularly those enhancing regulatory capacities and caregiver-child relationships, are critical to altering maladaptive trajectories and improving outcomes.